Schoology-based Training Module for Improving Teacher Competence in Making Classroom Action Research - Yahya Kristanto; Mawardi; Yari Dwikurnaningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Teachers as the front line in the development of the quality of education in Indonesia are considered by most groups to be still low. This study aims to develop a teacher competency improvement module to make classroom action research using Schoology. This study uses the Borg and Gall development research model integrated with the ADDIE model. Data collection techniques with interviews, questionnaires, rubrics, pre-test and post-test. The data analysis technique used descriptive categorical percentages and the Wilcoxon Signed Ranks Test. The results of the validation of material experts scored 84.17%, module design experts 85.57%, and training media experts 89%. Based on the results of expert validation, the module is considered very feasible to use. In the 16-teacher trial, this module was also proven to be successful in improving the teacher’s ability to make Classroom Action Research as indicated by an increase in the score of 30.9% from the pre-test 49% to 79.9% in the post-test with the acquisition of a significant value from the Wilcoxson test of 0.005 < 0, 05, this shows that the development of modules using Schoology is effective for improving teacher competence in making Classroom Action Research. This research implies that the development of this module can help teachers in making CAR so that they can improve teacher competence.